ANALISIS BREAK EVENT POINT (BEP) PADA PT. ES MUDA PERKASA DENGAN MENGGUNAKAN METODE HARGA POKOK PRODUKSI (HPP) - Amni, Chairul; Indrayani, Indrayani (Jurnal Akuntansi dan Keuangan, 2020)
The survival of the company or the growth of the company, one part of the planning of profit planning profit used in the company is Break Even Point (BEP), which explains the relationship between costs, production volume, selling price in order to obtain the results of the company's research. This pricing is one of the determinants of competition in the market with similar industries. PT. Es Muda Perkasa is a company engaged in the industry of making ice blocks. In the competition, PT. Es Muda Perkasa has an approved selling price sufficient to compete in the industrial world but the prices offered by PT. Mighty Ice Young is still low. This is of course difficult for companies to be able to compete because the pricing that is applied is only based on estimation, so the price determined is not in accordance with production costs. Therefore the company needs to return to how the strategy of determining the price so that it can be achieved maximally, the determination and achievement of the BEP of the company can reach within a specified time. This study aims to analyze Break Event Point (BEP) at PT. Es Muda Perkasa, by determining the optimal selling price of ice blocks. The research method used in this study uses the calculation of event break-even points using the method of calculating the cost of production. Data collection using collection of observations, interviews, and literature studies. The results of the study showed break-even (break-even point) PT. Perkasa Es Muda after selling beam products as many as 2400 blocks with a turnover obtained for BEP amounting to Rp.605,812 with a selling price of ice blocks of Rp. 18.496 / stem.